2015
DOI: 10.1002/micr.22462
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing facial contour deformities using stereoscopic thoracodorsal artery perforator adipofascial flaps

Abstract: Our results suggest that the stereoscopic TDAP adipofascial flaps with diligent secondary approaches may be a reliable alternative for aesthetic reconstruction of facial contour deformities. © 2015 Wiley Periodicals, Inc. Microsurgery 37:300-306, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Kim et al also reported uncertainty about the long-term volume loss of the transplanted tissue, when they transferred adipocutaneous tissue nourished by reverse vascular flow from the latissimus dorsi musculocutaneous perforator. 14 We think muscle denervation is also associated with long-term volume reduction.…”
Section: Discussionmentioning
confidence: 97%
“…Kim et al also reported uncertainty about the long-term volume loss of the transplanted tissue, when they transferred adipocutaneous tissue nourished by reverse vascular flow from the latissimus dorsi musculocutaneous perforator. 14 We think muscle denervation is also associated with long-term volume reduction.…”
Section: Discussionmentioning
confidence: 97%
“…At present, the popular and widely used endoscopic technology is effective in reducing incision scars and hiding incisions. In terms of the contour fullness and symmetry of the exposed parts of the body surface, it is particularly important to reconstruct defects after surgery for malignant tumors in the face, neck, or breast 5,6 . The thickness requirements of the flap for reconstruction of different anatomical parts of the head and neck vary greatly to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Few authors have used this perforator flap in head and neck reconstruction, despite the TDAP flap has all the qualities to be applied in the region (O'Connell et al, ). The TDAP is a thin and pliable flap, with a long pedicle usually spared from atherosclerotic changes (Kim et al, ; O'Connell et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The thoracodorsal artery perforator flap (TDAP) described by Angrigiani, Grilli, & Siebert (), based on perforators arising from the thoracodorsal artery, consists on the overlying skin and subcutaneous tissue but not on the underlying LD muscle. Despite these advantages, the TDAP flap is not yet widely used in the head and neck reconstruction (Chao, Yu, Skoracki, Demonte, & Hanasono, ; Guerra, Lyons, Dupin, & Metzinger, ; Kim et al, ; Lee & Mun, ; O'Connell, Bajwa, Schache, & Shaw, ; Sosin, De la Cruz, et al, ).…”
Section: Introductionmentioning
confidence: 99%